Integrated analysis of the functions and clinical implications of exosome circRNAs in colorectal cancer - Lei, Tianxiang; Zhang, Yongxin; Wang, Xiaofeng; Liu, Wenwei; Feng, Wei; Song, Wu (Frontiers in Immunology, 2022)
Background: Exosome circRNAs (Exo-circRNAs) regulate cancer progression and intercellular crosstalk in the tumor microenvironment. However, their biological functions and potential clinical importance in colorectal cancer (CRC) remain unknown. Methods：We used exoRBase data to identify significant differentially expressed Exo-circRNAs (Exo-DEcircRNAs) in CRC patients and healthy individuals. The least absolute shrinkage and selector operation algorithm, support vector machine-recursive feature elimination, and multivariate Cox regression analyses were used to select candidate Exo-circRNAs and construct a diagnostic model. Quantitative reverse transcription-polymerase chain reaction (qRT-PCR) analysis was performed to confirm the expression of Exo-circRNAs in the serum samples of CRC patients. Furthermore, we constructed an exosome circRNA-miRNA-mRNA network for CRC. Upregulated target mRNAs in the exosome competing endogenous RNA (Exo-ceRNA) network were used for functional and pathway enrichment analyses. We identified 22 immune cell types in CRC patients using CIBERSORT. Correlation analysis revealed the relationship between Exo-ceRNA networks and immune-infiltrating cells. Finally, using the Kaplan–Meier survival curve , prognostic upregulated target mRNAs were screened. We constructed a survival-related Exo-ceRNA subnetwork and explored the correlation between the Exo-ceRNA subnetwork and immune-infiltrating cells. Results：The constructed diagnostic model had a high area under the curve (AUC) value in both the training and validation sets (AUC = 0.744 and AUC = 0.741, respectively). qRT-PCR confirmed that the Exo-circRNAs were differentially expressed in CRC serum samples. We constructed Exo-ceRNA networks based on the interactions among seven upregulated Exo-DEcircRNAs, eight differentially expressed miRNAs, and twenty-two differentially expressed mRNAs in CRC. Functional enrichment analysis revealed that the upregulated target mRNAs were significantly enriched in cytoskeletal motor activity and the PI3K-Akt signaling pathway. Co-expression analysis showed a significant correlation between the Exo-ceRNA networks and immune cells. Additionally, based on the upregulated target gene (RGS2) , we constructed a survival-related Exo-ceRNA subnetwork (Exosome has_circ_0050334-has_miR_182_5p-RGS2). CIBERSORT results revealed that the Exo-ceRNA subnetwork correlated with M2 macrophages (P = 4.6e-07, R = 0.31). Conclusions：Our study identified an Exo-diagnostic model, established Exo-ceRNA networks, and explored the correlation between Exo-ceRNA networks and immune cell infiltration in CRC. These findings elucidate the biological functions of Exo-circRNAs and their potential clinical implications.